Adjunctive rifampicin to reduce early mortality from Staphylococcus aureus bacteraemia: the ARREST RCT - Thwaites, GE; Scarborough, M; Szubert, AJ; Concalves, P; Soares, M; Bostock, J; Nsutebu, E; Tilley, R; Cunningham, R; Grieg, J; Wyllie, SA; Wilson, P; et al. (NIHR Journals Library, 2018)
Background: Around 12,500 cases of Staphylococcus aureus bacteraemia occur each year in the United Kingdom, with an associated mortality of about 30%, yet the evidence guiding optimum management is poor. We hypothesise that adjunctive rifampicin will enhance killing of Staphylococcus aureus early in the course of antibiotic treatment of bacteraemia, sterilise infected foci and blood faster, and thereby reduce the risk of dissemination, metastatic infection and death. Design: A randomised, blinded, placebo controlled trial. Eligible patients will be randomised to two parallel arms in a 1:1 ratio: standard intravenous antibiotic therapy of the attending physician's choice plus either 14 days of placebo or rifampicin (900mg/24hrs if >60kg; 600mg/24hrs if <60kg). Setting: 29 large acute NHS Trusts. Target population: All adults (=18 years) with a pure culture of S. aureus (meticillin-susceptible or resistant) grown from their blood will be eligible. Patients will be excluded if they have received >96 hours of active antibiotic therapy for the current infection. Outcome measurements: The primary outcome will be death or bacteriological failure (microbiologically confirmed treatment failure or disease recurrence) by 12 weeks from randomisation. The secondary endpoints will include all-cause mortality through 14 days; duration of bacteraemia; death or clinically defined treatment failure or disease recurrence by 12 weeks adjudicated by an independent endpoint committee blind to treatment allocation; the development of rifampicin resistant S. aureus; modification of any drug treatment due to drug interactions; and serious adverse events and reactions. Healthcare-related resource use and EQ-5D will be collected during the trial to determine the cost-effectiveness of rifampicin for S. aureus bacteraemia treatment in the NHS. Sample size: Current data indicate 16% and 24% of all cases of S. aureus bacteraemia die by 14 days and 12 weeks respectively; a further 10% of patients have repeat isolation of S. aureus over the 12 weeks following initial bacteraemia. Assuming at least 80% power, two-sided alpha 0.025, and a 10% loss to follow-up by 12 weeks, we would need to randomise 940 patients to detect a 30% relative reduction in death/bacteriological failure by 12 weeks and a 45% reduction in death by 14 days. Sample size re-calculation in protocol version 5.0: With 12-week bacteriological failure/recurrence or death as the sole primary endpoint, the total sample size is now 770 patients (alpha=0.05, other assumptions as above).